2018
DOI: 10.1037/adb0000403
|View full text |Cite
|
Sign up to set email alerts
|

Who responds best to text-delivered cannabis use disorder treatment? A randomized clinical trial with young adults.

Abstract: Young adults ages 18 to 25 have the highest percentage (5%) of cannabis use disorder (CUD) among all age groups, and are the least likely to receive treatment compared with other age groups. Because this population is in need of creative approaches for treatment engagement, we tested Peer Network Counseling-txt (PNC-txt), a 4-week, automated text-delivered cannabis treatment that focuses on close peer relations with 96 treatment seeking young adults. Participants meeting CUD criteria were randomized to PNC-txt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Participants' mean age ranged from 16.3 to 29.8, and 47.6% were female. Twelve studies reported CU as the main outcome (Buckner et al, 2020;Elliott et al, 2014;Jacobus et al, 2018;Lee et al, 2010;Mason, Zaharakis, Russell, et al, 2018;Mason, Zaharakis, Moore, et al, 2018;Schaub et al, 2015;Shrier et al, 2018;Sinadinovic et al, 2020;Tossmann et al, 2011;Walton et al, 2013;Walukevich-Dienst et al, 2019) while the other five also include use of other drugs as an outcome. Becker as a secondary outcome (Buckner et al, 2020;Elliott et al, 2014;Jacobus et al, 2018;Schaub et al, 2015 andSinadinovic et al, 2020), and two studies (Shrier et al, 2018;Walton et al, 2013)…”
Section: Description Of Studies Contributing To Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' mean age ranged from 16.3 to 29.8, and 47.6% were female. Twelve studies reported CU as the main outcome (Buckner et al, 2020;Elliott et al, 2014;Jacobus et al, 2018;Lee et al, 2010;Mason, Zaharakis, Russell, et al, 2018;Mason, Zaharakis, Moore, et al, 2018;Schaub et al, 2015;Shrier et al, 2018;Sinadinovic et al, 2020;Tossmann et al, 2011;Walton et al, 2013;Walukevich-Dienst et al, 2019) while the other five also include use of other drugs as an outcome. Becker as a secondary outcome (Buckner et al, 2020;Elliott et al, 2014;Jacobus et al, 2018;Schaub et al, 2015 andSinadinovic et al, 2020), and two studies (Shrier et al, 2018;Walton et al, 2013)…”
Section: Description Of Studies Contributing To Data Analysismentioning
confidence: 99%
“…Interventions included 11 studies examining motivational interviewing (Becker et al, 2014;Buckner et al, 2020;Christoff & Boerngen-Lacerda, 2015;Gryczynski et al, 2020;Hernandez et al, 2019;Lee et al, 2010;Mason, Zaharakis, Moore, et al, 2018;Mason, Zaharakis, Russell, et al, 2018;Thompson Jr. et al, 2020;Walton et al, 2013;Walukevich-Dienst et al, 2019), one study evaluating counselling combined with MI (Shrier et al, 2018), one study evaluating counselling combined with MI and CBT (Schaub et al, 2015), another providing psychoeducation based on MI and CBT (Sinadinovic et al, 2020), and one study each using counselling (Tossmann et al, 2011), psychoeducation (Elliott et al, 2014), and cognitive training (Jacobus et al, 2018) as shown in Table 2. As depicted in Table 2, recruitment methods consisted of a national drug specialized website (Sinadinovic et al, 2020;Tossmann et al, 2011), local newspapers, radio and TV (Becker et al, 2014) (Gryczynski et al, 2020;Walton et al, 2013), inner crisis shelters (Thompson Jr. et al, 2020), and family court systems (Hernandez et al, 2019).…”
Section: Characteristics Of the Interventionsmentioning
confidence: 99%
“…In the last three years, there have been several studies examining the effectiveness of digitized interventions such as web-applications [77,78], text messaging [79], video games [80], and cognitive bias training [81]. Development of many of these promising interventions has been based on interventions such as MI [77, 82•,83], with the aim of effectively reducing substance use and substancerelated cravings and problems through the delivery of automated, personalized text messages [83][84][85].…”
Section: A Digital Strategiesmentioning
confidence: 99%
“…Positive studies have found that texting and web-based interventions can effectively reduce risky drinking and drinking frequency as well as lessen existing substance use [76,82]. However, the effects of some of these technology-based interventions may be limited, as one study found that digital interventions are more effective among highly-educated adolescents compared to less-educated adolescents [86], as well as among youth with less severe substance use disorders [85].…”
Section: A Digital Strategiesmentioning
confidence: 99%
“…Preliminary evidence from an RCT conducted in the USA showed that a 4-week text-delivered treatment reduced the proportion of the sample reporting cannabis-related relationship problems ( n = 51) significantly more than an assessment-only control ( n = 50). However, there was no reduction in frequency of cannabis use (Mason et al, 2018). Furthermore, retention was high with 96% of participants completing 3-month follow-up.…”
Section: Treatment Of Cannabis Use Disordersmentioning
confidence: 99%